2022
DOI: 10.1002/ange.202112769
|View full text |Cite
|
Sign up to set email alerts
|

Overlooked Factors Required for Electrolyte Solvents in Li–O2 Batteries: Capabilities of Quenching 1O2 and Forming Highly‐Decomposable Li2O2

Abstract: Although sufficient tolerance against attack by superoxide radicals (O 2 À ) has been mainly recognized as an important property for Li-O 2 battery (LOB) electrolytes, recent evidence has revealed that other critical factors also govern the cyclability, prompting a reconsideration of the basic design guidelines of LOB electrolytes. Here, we found that LOBs equipped with a N,N-dimethylacetamide (DMA)based electrolyte exhibited better cyclability compared with other standard LOB electrolytes. This superior cycla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The retreating front during charging process has been shown to also locate at the Li 2 O 2 /electrolyte interface. 32 Therefore, because of the reaction between Li 2 O 2 and the electrolyte, new byproducts should be localized at the Li 2 O 2 /electrolyte interface, which is continuously exposed during charging (Figure 6b). To verify this speculation, we conducted ToF-SIMS measurements on the sample surface after one discharge−charge cycle.…”
Section: X-ray Photoelectron Spectroscopy (Xps) the Edx Andmentioning
confidence: 99%
See 3 more Smart Citations
“…The retreating front during charging process has been shown to also locate at the Li 2 O 2 /electrolyte interface. 32 Therefore, because of the reaction between Li 2 O 2 and the electrolyte, new byproducts should be localized at the Li 2 O 2 /electrolyte interface, which is continuously exposed during charging (Figure 6b). To verify this speculation, we conducted ToF-SIMS measurements on the sample surface after one discharge−charge cycle.…”
Section: X-ray Photoelectron Spectroscopy (Xps) the Edx Andmentioning
confidence: 99%
“…This result is reasonable given that the discharge reaction occurs at the Li 2 O 2 /electrolyte interface in this system. 32 Concretely, because Li 2 CO 3 , a side-reaction product, is constantly generated at the growing interface, it is uniformly distributed inside the discharge products, as schematically shown in Figure 6a. This conclusion is consistent with that deduced from the previously discussed ToF-SIMS analysis results.…”
Section: X-ray Photoelectron Spectroscopy (Xps) the Edx Andmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has recently been reported that the amide-based electrolytes exhibit a good cycling performance. 8 On the other hand, one of the attractions of nonvolatile ionic liquids (ILs) is that they exhibit various physical…”
Section: Introductionmentioning
confidence: 99%